Study of a Welding Pool Harmonic Oscillations Influence on the Welded Metal Hardness and Weld Bead Width - Lebedev V. A.; Solomiichuk T. G.; Novykov S. V. (Журнал інженерних наук, 2019)
The comparison results of the hardness measuring of welded metal and the heat-affected zone of the eight welded beads from low-carbon steel obtained by surfacing CO2/MAG with welding bath oscillation influence at values of amplitude equaled 0.5 mm (frequency values were 2.5, 3.0, 4.0, and 4.5 Hz) and 4.0 mm (frequency values were 3.7, 3.8, 3.9, and 4.0 Hz) are presented. A technological mode was the same for all specimens. The special influence of amplitude on the hardness value is noted. The structural metal components of the beads with a maximum hardness value are presented. An analytical calculation of the beads width depending on the value amplitude equaled 6 mm and oscillation frequency (values equal 2.5, 3.0, 4.0, and 4.5 Hz) of the weld pool is presented. A comparative analysis of the calculated and experimental values of the beads width is given. The influence of the oscillation frequency on the width value is noted.